A meta‐analysis of lesser prairie‐chicken nesting and brood‐rearing habitats: Implications for habitat management. (5th August 2013) - Hagen, Christian A.; Grisham, Blake A.; Boal, Clint W.; Haukos, David A.
ABSTRACT The distribution and range of lesser prairie‐chicken (Tympanuchus pallidicinctus) has been reduced by >90% since European settlement of the Great Plains of North America. Currently, lesser prairie‐chickens occupy 3 general vegetation communities: sand sagebrush (Artemisia filifolia), sand shinnery oak (Quercus havardii), and mixed‐grass prairies juxtaposed with Conservation Reserve Program grasslands. As a candidate for protection under the Endangered Species Act, there is a need for a synthesis that characterizes habitat structure rangewide. Thus, we conducted a meta‐analysis of vegetation characteristics at nest sites and brood habitats to determine whether there was an overall effect (Hedges' d) of habitat selection and to estimate average (95% CI) habitat characteristics at use sites. We estimated effect sizes (di) from the difference between use (nests and brood sites) and random sampling sites for each study (n = 14), and derived an overall effect size (d++). There was a general effect for habitat selection as evidenced by low levels of variation in effect sizes across studies and regions. There was a small to medium effect (d++ = 0.20–0.82) of selection for greater vertical structure (visual obstruction) by nesting females in both vegetation communities, and selection against bare ground (d++ = 0.20–0.58). Females with broods exhibited less selectivity for habitat components except for vertical structure. The variation of d++ was greater during nesting than brooding periods, signifying a seasonal shift in habitat use, and perhaps a greater range of tolerance for brood‐rearing habitat. The overall estimates of vegetation cover were consistent with those provided in management guidelines for the species. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.